Comparative Vaccination Service Management of COVID-19 in Central Sulawesi - Mangagasing, Nasir; Nuraisyah, Nuraisyah; Husain, Sulfitri; Rachmad, Rachmad (Interdisciplinary Social Studies, 2022)
Background: Based on the initial observations of the study, it was obtained that the management of the COVID-19 vaccination service doses 1 and 2 in Sigi Regency and Palu City experienced different achievement targets. This can be seen from the achievement of vaccination in the district. Sigi at the 1st dose reached 74.08% and the second still reached 49.94%. Meanwhile, the vaccination achievement of Palu City at dose 1 had reached 92.37% and at dose 2 it was 71.39%. This is because there are still many people in Sigi Regency who are reluctant to get vaccinated, some of the Sigi people who live on the border mostly carry out vaccinations in Palu City, data entry is late, and there are still many isolated areas that are difficult to reach. Meanwhile in Palu, the management of vaccine services has been running well and according to the predetermined targets. Aim: This research plan aims to compare the management of the first and second dose of COVID-19 vaccination services in middle Sulawesi. Method: A qualitative approach with a descriptive design is the research methodology adopted. A comparison study is the kind of descriptive research technique utilized. Findings: Based on the results of the study, it was found that the management of the COVID-19 vaccination service doses 1 and 2 in Sigi Regency was less than optimal, while Palu City was running well.